2012
DOI: 10.1073/pnas.1211076109
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the sheddase function of human meprin β metalloproteinase at the plasma membrane

Abstract: Ectodomain shedding at the cell surface is a major mechanism to regulate the extracellular and circulatory concentration or the activities of signaling proteins at the plasma membrane. Human meprin β is a 145-kDa disulfide-linked homodimeric multidomain type-I membrane metallopeptidase that sheds membrane-bound cytokines and growth factors, thereby contributing to inflammatory diseases, angiogenesis, and tumor progression. In addition, it cleaves amyloid precursor protein (APP) at the β-secretase site, giving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 59 publications
3
76
1
Order By: Relevance
“…Since BACE-1 is not capable in directly generating this peptide, a suggested model for the emergence of N-terminal truncation is the subsequent cleavage of the N-terminus of BACE generated Aβ1-x by either Aβ degrading enzymes like insulin-degrading enzymes (IDE) or neprilysin or the aminopeptidase A (APA) (Arai et al, 1999; Wiltfang et al, 2001; Wang et al, 2006). A candidate directly generating N-terminally truncated Aβ independent of BACE-1 is the metalloprotease meprin β. Meprin β is a multi-domain type I transmembrane protein, member of the astacin family of zinc-endopeptidases that is predominantly present as a dimer at the cell surface (Arolas et al, 2012; Figure 2). In 2011 meprin β was introduced as an alternative enzyme involved in APP processing (Jefferson et al, 2011).…”
Section: Alternative App Processingmentioning
confidence: 99%
“…Since BACE-1 is not capable in directly generating this peptide, a suggested model for the emergence of N-terminal truncation is the subsequent cleavage of the N-terminus of BACE generated Aβ1-x by either Aβ degrading enzymes like insulin-degrading enzymes (IDE) or neprilysin or the aminopeptidase A (APA) (Arai et al, 1999; Wiltfang et al, 2001; Wang et al, 2006). A candidate directly generating N-terminally truncated Aβ independent of BACE-1 is the metalloprotease meprin β. Meprin β is a multi-domain type I transmembrane protein, member of the astacin family of zinc-endopeptidases that is predominantly present as a dimer at the cell surface (Arolas et al, 2012; Figure 2). In 2011 meprin β was introduced as an alternative enzyme involved in APP processing (Jefferson et al, 2011).…”
Section: Alternative App Processingmentioning
confidence: 99%
“…Meprin b, a multidomain type I transmembrane metalloprotease, is an initiator of RIP, and structural studies revealed dimeric formation of the protease with the active site in proximity to the cell surface (2)(3)(4). In addition, meprin b can be shed from the cell surface by ADAM10/ 17, resulting in a soluble active protease, which for instance is important for mucus detachment in the small intestine (5).…”
mentioning
confidence: 99%
“…Therefore the observed dimer in the asymmetric unit is possibly a crystallographic artifact of no physiological relevance. In contrast to the meprin MAM domain (Arolas et al., 2012), which contains five cysteine residues in the MAM domain of NRP1, no intermolecular disulfide bond can be formed as the four cysteine side chains present form intramolecular disulfide bonds, thus eliminating cysteine-dependent oligomerization as a mechanism of NRP1 self-association. However, it has recently been postulated that the integrity of the intramolecular disulfide bonds might regulate NRP oligomerization (Barton et al., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Overlaying the MAM domain structure from RPTPmu (PDB: 2C9A, residues 1–187, 25% sequence identity to NRP1) (Aricescu et al., 2006) and meprin (PDB: 4GWM, residues 257–428, 29% sequence identity to NRP1) (Arolas et al., 2012) to that of NRP1 gives an RMSD for Cα atoms of 1.6 Å and 1.7 Å, respectively (Figure 3B). The β strands overlap very well while the flexible loops are the main source of variation between the three structures.…”
Section: Resultsmentioning
confidence: 99%